Orthopaedic Fixation Devices Used in Children: A Radiologist's Guide - Allen, Hailey; Davis, Kirkland W.; Noonan, Kenneth; Endo, Yoshimi; Nguyen, Jie C. (Seminars in Musculoskeletal Radiology, 2018)
Fractures are common in children with some requiring surgical reduction and fixation to maintain anatomical alignment. Although various surgical techniques and principles are shared between children and adults, certain unique considerations in children can influence the surgical approach and device selection. In particular, for skeletally immature children, it is of utmost importance to protect certain critical open growth plates because permanent injury can produce severe growth disturbances. The often robust healing response and potential limited patient compliance can also influence the treatment algorithm and decision making. Commonly encountered orthopaedic fixation devices, including screws, intramedullary devices, and plates, are reviewed with an emphasis on their mechanism and application in children. Additional miscellaneous devices that are commonly used to treat malalignment and guide bone growth including epiphysiodesis plates, proximal femur osteotomy plates, and spinal magnetic growing rods are also reviewed. The goal of this article is to provide a basic understanding of the principles and mechanisms of different types of pediatric orthopaedic devices and thereby improve the radiologist's diagnostic confidence and allow better anticipation of complications.
Keywords: fracture fixation; growth disturbance; magnetic nail and rod; pediatric growth plate; screws